Prognostic Significance of Microvessel Density as Assessed by anti CD34 Monoclonal Antibody in Invasive Ductal Carcinoma of Breast - Bhawna Agnani; Ranjana Solanki; Maryem Ansari; Sankalp Agnani (Asian Pacific Journal of Cancer Biology, 2020)
Context and Aim: Breast carcinoma is one of the leading causes of cancer related mortality in females. A number of established prognostic indicators exist for breast cancer. One potential indicator of adverse prognosis in breast cancer is tumor induced angiogenesis. Hematogenous spread of tumor cells is quantitatively related to microvessel density (MVD). This study aims to find possible association of microvessel density with other recognized prognostic factor such as patient age, tumor size, lymph node status, histologic grade, Nottingham Prognostic Index (NPI), vascular invasion, hormone receptor status and HER2/Neu expression in breast carcinoma. Methods and Materials: This is a cross sectional, laboratory based descriptive type of observational study. This study was carried out in the Department of Pathology, SMS medical college. In our study we did histological evaluation of mastectomy specimen of breast cancer including ER, PR and Her 2 status and calculated the microvessel density (MVD) in appropriate section by applying IHC. MVD correlation with other clinicopathological parameters was done. Stastical analysis used in this study include Fischer Exact test and Chi Square test. Results: A significant correlation was obtained between MVD and tumor size, lymph node metastasis, lymphovascular invasion, histologic grade and NPI (P value of 0.01). Conclusions: Angiogenesis is an important component of cancer growth, invasion and metastasis. Therefore, inhibition of angiogenesis is an attractive strategy for treatment of cancer. The correlation of MVD with prognosis suggests the utility of antiangiogenic drugs in breast cancer patients with high angiogenesis